Botrytis – The Fungus, the Pathogen and Its Management in Agricultural Systems 2015
DOI: 10.1007/978-3-319-23371-0_19
|View full text |Cite
|
Sign up to set email alerts
|

Ripening of Tomato Fruit and Susceptibility to Botrytis cinerea

Abstract: Botrytis cinerea causes gray mold decay in the ripe fruit of many plant species leading to signifi cant economic losses for the producers, distributers and consumers of fresh and stored produce. This chapter summarizes current knowledge about the biology of a model fl eshy fruit, tomato, during B. cinerea infections. The information presented emphasizes how ripening regulation and events in the host infl uence resistance when fruit are unripe and susceptibility when fruit are ripe. Fruit ripening regulators (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 193 publications
(266 reference statements)
0
33
0
Order By: Relevance
“…However, in the ripe stage, strawberries are highly susceptible and decay rapidly. Fruit susceptibility to fungal disease increases as ripening progresses; hence, B. cinerea appears to promote susceptibility in unripe fruit by activating specific ripening‐related processes (Blanco‐Ulate et al , ). In tomato fruit, master transcriptional regulators of ripening have been shown to have different roles in disease susceptibility.…”
Section: Relevance Of Ripening Processes To Botrytis Cinerea Infectiomentioning
confidence: 99%
See 3 more Smart Citations
“…However, in the ripe stage, strawberries are highly susceptible and decay rapidly. Fruit susceptibility to fungal disease increases as ripening progresses; hence, B. cinerea appears to promote susceptibility in unripe fruit by activating specific ripening‐related processes (Blanco‐Ulate et al , ). In tomato fruit, master transcriptional regulators of ripening have been shown to have different roles in disease susceptibility.…”
Section: Relevance Of Ripening Processes To Botrytis Cinerea Infectiomentioning
confidence: 99%
“…Cell wall degradation benefits B. cinerea as it reduces mechanical barriers to infection and spread, increases the possibilities of bruising (e.g. leading to more wounds for pathogen entry) and provides the fungus with access to simple sugars as a carbon source (Blanco‐Ulate et al , ; Blanco‐Ulate et al , ; Brummel and Harpster, ).…”
Section: Relevance Of Ripening Processes To Botrytis Cinerea Infectiomentioning
confidence: 99%
See 2 more Smart Citations
“…Yet another crucial question is whether the transition from the dormant to the virulent state could favor the fruit ripening process necessary for the infection and subsequent growth of pathogenic fungi. Blanco‐Ulate et al., and Powell (2016) investigated this case during fungi infection of tomatoes. They showed that Botrytis contributed to the ripening and sensitivity of tomatoes.…”
Section: Recent Developments In the Knowledge Of Postharvest Fungal Infection Of Fruitmentioning
confidence: 99%